Structural and functional brain network correlates of depressive symptoms in premanifest Huntington's disease - McColgan, Peter (Hum Brain Mapp, 2017)
Depression is common in premanifest Huntington's disease (preHD) and results in significant morbidity. We sought to examine how variations in structural and functional brain networks relate to depressive symptoms in premanifest HD and healthy controls. Brain networks were constructed using diffusion tractography (70 preHD and 81 controls) and resting state fMRI (92 preHD and 94 controls) data. A sub‐network associated with depression was identified in a data‐driven fashion and network‐based statistics was used to investigate which specific connections correlated with depression scores. A replication analysis was then performed using data from a separate study. Correlations between depressive symptoms with increased functional connectivity and decreased structural connectivity were seen for connections in the default mode network (DMN) and basal ganglia in preHD. This study reveals specific connections in the DMN and basal ganglia that are associated with depressive symptoms in preHD. Hum Brain Mapp 38:2819–2829, 2017. © 2017 The Authors Human Brain Mapping Published by Wiley Periodicals, Inc.